Subsequential Results on Uniform Statistical Convergence - Yurdakadim, Tuğba; Miller-Wan Wieren, Leila (Sarajevo Journal of Mathematics, 2024)
In this paper, we present some relationships between convergence and uniform statistical convergence of a given sequence and its subsequences. The results concerning uniform statistical convergence presented here are also closely related to earlier results regarding statistical convergence and almost convergence of sequences, and are dealing with measure and in a minor case with category. Finally, we present a Cauchy type characterization of uniform statistical convergence and a result concerning uniform statistical convergence of subseries of a series.